2015
DOI: 10.5194/amtd-8-9209-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smithsonian Astrophysical Observatory Ozone Mapping and Profiler Suite (SAO OMPS) formaldehyde retrieval

Abstract: Abstract. This paper presents our new formaldehyde (H2CO) retrievals, obtained from spectra recorded by the nadir instrument of the Ozone Mapping and Profiler Suite (OMPS) flown on-board NASA's Suomi National Polar-orbiting Partnership (SUOMI-NPP) satellite. Our algorithm is similar to the one currently in place for the production of NASA's Ozone Monitoring Instrument (OMI) operational H2CO product. We are now able to produce a consistent set of long term data from two different instruments that share a simila… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…However, OMI has suffered from a so-called "row anomaly" and lost several cross-track positions data (Boersma et al, 2011). In this study, we use USTC-OMI tropospheric NO2 products (Liu et al, 2016;Su et al, 2017 (Dittman et al, 2002;Seftor et al, 2014;González Abad et al, 2016). Its equator crossing time in the ascending node is 13:30…”
Section: Omi and Omps Satellite Datamentioning
confidence: 99%
“…However, OMI has suffered from a so-called "row anomaly" and lost several cross-track positions data (Boersma et al, 2011). In this study, we use USTC-OMI tropospheric NO2 products (Liu et al, 2016;Su et al, 2017 (Dittman et al, 2002;Seftor et al, 2014;González Abad et al, 2016). Its equator crossing time in the ascending node is 13:30…”
Section: Omi and Omps Satellite Datamentioning
confidence: 99%
“…The GCAS instrument (Kowalewski and Janz, 2014) was deployed on the NASA King Air B200 aircraft as part of the campaign's airborne remote sensing payload, which also included the NASA High Spectral Resolution Lidar (HSRL) instrument (Hair et al, 2008) for aerosol studies. GCAS operates in a similar fashion to GeoTASO, using a 2-D CCD array detector to map slant columns of NO 2 in two dimensions.…”
Section: Gcasmentioning
confidence: 99%
“…Finally, Zeng et al () showed that four global chemistry models underestimated column HCHO by approximately 50% in the Southern Hemisphere, as compared to FTIR observations, suggesting that these models lack a significant source of HCHO. It is imperative to evaluate the vertical columns of these CTMs, particularly in remote locations, as many satellite retrievals use output from these models to correct for biases in the retrieval (e.g., De Smedt et al, ; González Abad et al, , ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%